1983
DOI: 10.3109/00016358309162329
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of Induced Keratinization in Sulcular Gingival Epithelium in Rhesus Monkeys

Abstract: Gingival sulcular epithelium--which in primates normally does not keratinize--can be induced to undergo keratinization by prolonged intensive antibacterial therapy. Three months before biopsy the teeth of two adult male rhesus monkeys were scaled and polished, and for 5 days the monkeys were given intravenous injections of 75 mg Achromycin daily. Their teeth were subsequently subjected to daily cleaning and polishing. The presumably in-situ-keratinized sulcular epithelium was examined by transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…AIthoug this may be an important finding itself, its bearing on the interpretation of the results of the present study is rather limited, given the absence of a significant correlation between initial and final stage in the respects tnentioned above. However, a possibly pre-existing indammatory infiltrate and the state of the epithelium tiiay have had some bearing on the different rates of development of gingivitis in the 2 groups (Schroeder et al, 1975, Kristoffersen et al, 1983, An analysis of plaque cotnposition was outside the scope of the present study. The few reports on plaque composition found in the literature either reveal no great differences in this respect between DS children and controls or involved institutionalized children (Reuland-Bosma & Van Dijk 1986), It is more likely that the host reaction in DS children with their functional defects in PMN, tnonocytes and lymphocytes, is responsible for the difference in gingival inflammation found (Wittingham et al, 1977, Barkin et al, 1980a.…”
Section: Discussionmentioning
confidence: 87%
“…AIthoug this may be an important finding itself, its bearing on the interpretation of the results of the present study is rather limited, given the absence of a significant correlation between initial and final stage in the respects tnentioned above. However, a possibly pre-existing indammatory infiltrate and the state of the epithelium tiiay have had some bearing on the different rates of development of gingivitis in the 2 groups (Schroeder et al, 1975, Kristoffersen et al, 1983, An analysis of plaque cotnposition was outside the scope of the present study. The few reports on plaque composition found in the literature either reveal no great differences in this respect between DS children and controls or involved institutionalized children (Reuland-Bosma & Van Dijk 1986), It is more likely that the host reaction in DS children with their functional defects in PMN, tnonocytes and lymphocytes, is responsible for the difference in gingival inflammation found (Wittingham et al, 1977, Barkin et al, 1980a.…”
Section: Discussionmentioning
confidence: 87%
“…The reason for an earlier and a more rapid gingival response to denial plaque is not known; abnormalities in host defense may be of importance (Breg 1977). A faster gingival inflammation may aiso be the result of aberrant morphology of the gingival epithelium (Cohen et al 1961. Kristoffersen et al 1983, The presence in DS of systemic alterations affecting connective tissue and vascularisation, has been suggested (Cohen et al 1961, Claycomb et al 1970, Kontras & Bodenbender 1966.…”
mentioning
confidence: 99%
“…However, with a strict regimen of oral hygiene and antibiotics in monkeys it has been shown that the sulcular epithelium can become keratinized (Kristoffersen, Caffesse et al 1983). The base of the gingival sulcus gives rise to the junctional epithelium.…”
Section: VIImentioning
confidence: 99%